O-151 Detailed characterization of infertile men with idiopathic versus unexplained infertility: a single-center experience. (6th August 2021) - Boeri, L; Candela, L; Pozzi, E; Belladelli, F; Capogrosso, P; Cazzaniga, W; Costa, A; Fallara, G; Schifano, N; Cignoli, D; Ventimiglia, E; Alfano, M; et al.
Abstract: Study question: We aimed to investigate the rate of and the clinical characteristics of men with idiopathic versus unexplained infertility from a cohort of white-European men. Summary answer: Approximately 20% and 5% of men evaluated for primary couple's infertility depicted characteristics suggestive for idiopathic and unexplained infertility, respectively. What is known already: Male factor infertility (MFI) can be associated with clinical, hormonal and genetic diseases, but MFI is idiopathic in almost 30% of cases. Study design, size, duration: Data from 3098 infertile men (according to WHO definition) consecutively evaluated between 2003-2020 at a single academic centre were analysed and compared with those of 103 fertile controls. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Idiopathic infertility was defined for pathological semen analysis but normal physical examination and endocrine, genetic and biochemical laboratory testing. Unexplained infertility is defined as infertility of unknown origin with normal sperm parameters. Participants/materials, setting, methods: Testicular volume (TV) was assessed with a Prader's orchidometer. Serum hormones and sperm DNA fragmentation index (SDF) were measured in every patient. Vitamin D3 (VitD) deficiency was considered for vitD levels <20 ng/mL. Semen analyses were based on the 2010 WHO reference criteria. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Main results and the role of chance: Overall, 570 (18.5%) and 154 (5.0%) patients depicted criteria suggestive for either idiopathic or unexplained primary infertility, respectively. Groups were similar in terms of age, BMI, CCI, recreational habits, circulating serum hormones and SDF. Testicular volume was lower in men with idiopathic vs. unexplained infertility [median (IQR) 20 (15-25) vs. 20 (17-25); p < 0.001]; more idiopathic than unexplained infertile men depicted TV < 15ml (23.4% vs. 12%; p < 0.01). Similarly, vitD levels were lower [22 (17-28) vs. 27 (21-42) ng/mL; p < 0.001] in idiopathic vs. unexplained infertile men, with a higher rate of pathologic VitD levels in the same group (42.1% vs. 10%; p = 0.04). When compared to fertile controls, groups were similar in terms of age, BMI, CCI and serum hormones values. TV was larger in fertile controls than idiopathic and unexplained infertile men (all p < 0.01). At multivariable logistic regression analysis only vitD deficiency (OR 8.1, p = 0.03) was found to be associated with idiopathic infertility after accounting for age, BMI, testosterone values and TV. Limitations, reasons for caution: The small number of fertile controls may raise the possibility of biases. Wider implications of the findings: Idiopathic and unexplained infertility were identified in approximately 20% and 5% of men evaluated, respectively. Idiopathic infertile men showed lower TV and lower vitD values compared to men with unexplained infertility. Future studies are needed to develop a more tailored management to these difficult MFI cases. Trial registration number: .